Penguatan Tata Kelola Data Ekonomi BUMDes Berbasis Dashboard Informasi Desa di Desa Tabongo Timur - Muhammad Rifai Katili; Lanto Ningrayati Amali; Sri Nilawaty Lahay; Mohamad Syafri Tuloli (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2026)
This community service activity was carried out to strengthen the economic data governance of BUMDes Sinar Usaha toward the development of a village information dashboard in Tabongo Timur Village, Tabongo Subdistrict, Gorontalo Regency. This BUMDes already has active business units, including its flagship product, Sacha Inchi oil "Sachita"; however, data on business units, activity volumes, partners, customers, workforce, and training remained scattered and unintegrated, making it difficult to use as a basis for decision-making. The activity employed a training and mentoring approach based on Participatory Rural Appraisal (PRA) combined with dashboard prototype development using a Research and Development (RD) Agile/Scrum approach, encompassing initial coordination, data needs analysis, economic indicator mapping, data governance training, assistance in completing standardized forms, dashboard prototype development, and limited trials involving 12 participants consisting of BUMDes management and village officials. The outcomes of the activity include the establishment of BUMDes economic data indicators, standardized recording formats, a web-based village economic information dashboard prototype named "Tomini-Desk" displaying indicators of business units, partners, workforce, and training, as well as improved understanding among BUMDes management and village officials regarding the importance of economic data, as reflected in a user feedback evaluation score of 87%. This dashboard helps present village economic information in a more concise, visual, and easily understandable manner as a basis for decision-making for BUMDes management and village government.